IN VITRO PLANT REGENERATION STUDIES USING HYPOCOTYL EXPLANT OF BRINJAL (SOLANUM MELONGENA) - PUJA RATTAN,; SANJEEV KUMAR,; R. K. SALGOTRA, (The Bioscan, 2015)
The present study was done to standardize the protocol of embryo rescue technique in which the seeds of indigenous collection of Solanum melongena were used as explants. The explants hypocotyle was cultured on MS media supplemented with different combinations of auxins and cytokinins such as BAP (1 to 2.5 mg/l)+ IAA (0.2 to 0.4 mg/l) and Kinnetin (1 to 2.5 mg/l)+ IAA (0.2 to 0.4 mg/l) for shoot regeneration. Callus initiation and shoot initiation was observed after 15 - 20 days and 25days of inoculation, respectively on media supplemented with BAP-IAA. While, it took 25 and 30-35 days for callus initiation and shoot initiation, respectively on media supplemented with Kinnetin-IAA. The highest shoot regeneration (65.12%) was observed on MS medium supple- mented with 2mg/l BAP+ 0.3mg/l IAA after 25 days of inoculation. For root regeneration, regenerated shoots were transferred to root regeneration medium having MS medium supplemented with different concentration of auxins IAA (0.5-1mg/l) and IBA (0.5-1mg/l), so as to obtain the complete plantlets. The highest root regeneration was observed when MS medium was supplemented with IBA (1mg/lt). Hence the plant regeneration from hypocotyle of brinjal was observed to be influenced by different combinations and concentrations of auxins and cytokinins.